Empowerment of Integrated Health Post Cadres through Fish Nugget Processing to Prevent Anemia in Pregnant Women - Awatiful Azza; Danu Indra Wardhana (UNUSA Press, 2021)
Fish is a source of nutrition that is cheap and easy to get, especially in Jember Regency. One of the health problems experienced by teenage girls and pregnant women is anemia. Anemia can be prevented by consuming adequate and diverse nutrients. However, the society at Darungan Dusun (Dusun is lower than the village in Indonesia's administrational hierarchy) did not know how to make exciting and not boring processed food. Fish nugget is creations from tuna or catfish to increase fish consumption coverage in society. This activity was carried out in the Integrated Health Post at Darungan Dusun Kemuning Lor Village, Jember Regency. There were fourteen of the integrated health post cadres and pregnant women who participated in this activity. Community service methods used demonstrations and counseling. The counseling and demonstration of fish nugget processing improve knowledge in Integrated Health Post cadres and pregnant women. Furthermore, it can prevent anemia in pregnant women. There should be support and participation from the local government for the sustainability of this activity.